A Possible Role for Idiotype/Anti-idiotype B–T Cell Interactions in Maintaining Immune Memory - Seledtsov, Victor I.; Seledtsova, Galina V. (Frontiers in Immunology, 2017)
Variable regions of both B-cell receptors (BCRs) and T-cell receptors (TCRs) are completely formed in the postnatal period, and, consequently, no innate immune tolerance against these structures exists in adulthood. Indeed, antibodies (Abs) specific to TCRs have been found in both animals and humans. These facts clearly indicate the existence of B cells able to directly interact with T cells through binding of BCRs to TCRs without implicating Major Histocompatibility Complex (MHC) molecules. A novel paradigm is proposed in that the immune memory is based on idiotype (Id)/anti-idiotype (anti-Id) interactions occurring between BCRs and TCRs following clearance of the antigen (Ag) that elicited immune responses. It is envisaged that direct contact between memory T and B cells could provide costimulatory signals needed to sustain viability, growth and differentiation of the interacting immune cells. In contrast, plasma cells originating from memory B-cells could produce anti-TCR Abs that inhibit direct BCR-to-TCR interactions, thereby down-regulating the B-to-T-cell contact-based immune memory via a negative feedback mechanism.